Trends in Cancer Treatment for Oral Cavity, Oropharynx, and Larynx in 2016 Versus 2009: SEER Patterns of Care Studies. (June 2022) - Weeks, Kristin S.; Lynch, Charles F.; Pagedar, Nitin
Purpose: To determine if there was a higher percentage of patients treated surgically and with advanced radiotherapy in 2016 (N = 897) versus 2009 (N = 1136), the patient and tumor characteristics associated with surgical care and advanced radiotherapy, and if chemotherapy or targeted agent use varied over time for squamous cell carcinoma of the head and neck. Methods: We utilized Surveillance Epidemiology and End Results Patterns of Care datasets. Rao-Scott Chi-square tests and logistic regressions were applied to determine differences in surgery, advanced radiotherapy (RT), and chemotherapy by year. Results: There was a lower prevalence of surgery only treatment in 2016 versus 2009 with exception of oral cavity stages IVB/IVC and unknown, and larynx stage unknown. Advanced RT was more common in 2016 for patients receiving definitive RT among all sites, excluding stages I/II glottic larynx. Among each site (oral cavity, oropharynx, and larynx) lower stage was associated with increased odds of surgery. Among each site, advanced RT was more common in patients receiving definitive versus postoperative RT. For the larynx site, 2016 versus 2009 was associated with greater odds of advanced RT. Systemic treatment with fluorouracil, taxanes, or cetuximab was less prevalent in 2016. Conclusion: In 2016 versus 2009, there was largely not a higher percentage of patients treated surgically. There was a higher prevalence of advanced RT for definitive care. Further investigations of these patterns are needed, including trend analysis.